Allogeneic haematopoietic stem cell transplantation resets T‐ and B‐cell compartments in sickle cell disease patients. Issue 4 (23rd April 2022) - Jarduli‐Maciel, Luciana Ribeiro; de Azevedo, Júlia Teixeira Cottas; Clave, Emmanuel; Costa, Thalita Cristina de Mello; Arruda, Lucas Coelho Marlière; Fournier, Isabelle; Palma, Patrícia Vianna Bonini; Lima, Keli Cristina; Elias, Juliana Bernardes; Stracieri, Ana Beatriz PL; Pieroni, Fabiano; Cunha, Renato; et al.
Abstract: Objectives: Allogeneic haematopoietic stem cell transplantation (allo‐HSCT) is the only currently available curative treatment for sickle cell disease (SCD). Here, we comprehensively evaluated the reconstitution of T‐ and B‐cell compartments in 29 SCD patients treated with allo‐HSCT and how it correlated with the development of acute graft‐versus‐host disease (aGvHD). Methods: T‐cell neogenesis was assessed by quantification of signal‐joint and β‐chain TCR excision circles. B‐cell neogenesis was evaluated by quantification of signal‐joint and coding‐joint K‐chain recombination excision circles. T‐ and B‐cell peripheral subset numbers were assessed by flow cytometry. Results: Before allo‐HSCT (baseline), T‐cell neogenesis was normal in SCD patients compared with age‐, gender‐ and ethnicity‐matched healthy controls. Following allo‐HSCT, T‐cell neogenesis declined but was fully restored to healthy control levels at one year post‐transplantation. Peripheral T‐cell subset counts were fully restored only at 24 months post‐transplantation. Occurrence of acute graft‐versus‐host disease (aGvHD) transiently affected T‐ and B‐cell neogenesis and overall reconstitution of T‐ and B‐cell peripheral subsets. B‐cell neogenesis was significantly higher in SCD patients at baseline than in healthy controls, remaining high throughout the follow‐up after allo‐HSCT. Notably, after transplantation SCD patients showed increased frequencies of IL‐10‐producing B‐regulatory cells and IgM + memory B‐cell subsets compared with baseline levels and with healthy controls. Conclusion: Our findings revealed that the T‐ and B‐cell compartments were normally reconstituted in SCD patients after allo‐HSCT. In addition, the increase of IL‐10‐producing B‐regulatory cells may contribute to improve immune regulation and homeostasis after transplantation. Abstract : In this study, we found that allogeneic hematopoietic stem cell transplantation resets the T‐ and B‐cell compartments in sickle cell disease patients. In addition, the increase of IL‐10‐producing B‐regulatory cells after transplantation may contribute to improve immune regulation and homeostasis.